2022
DOI: 10.2174/1381612828666220902115437
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Protects Diabetes Mellitus Rats Complicated with Cardiomyopathy through TGF-β1/JNK Signaling Pathway

Abstract: Background: Epigallocatechin gallate (EGCG) is the main component of rhubarb tannin, with antioxidant, anti-angiogenic, anti-cancer and antiviral activities. Diabetes mellitus (DM) is a high blood sugar and protein metabolism disorder syndrome, which is caused by absolute or relative factors, such as deficiency of insulin and oxidative stress. Diabetes cardiomyopathy (DCM) is one of the most frequent complications of DM. Objective: This study aims to explore whether EGCG can improve diabetic complication, my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…166 TGF-β1/JNK was related to myocardial fibrosis in DCM. 167 In addition, JNK was involved in regulating NLRP3 inflammasome activation in macrophages. 168 IL-1β, IL-6, and TNF-α could stimulate JAK/STAT after binding to the receptor, thereby initiating the expression of downstream inflammation-related target genes.…”
Section: Cytokines Impact On Heart Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…166 TGF-β1/JNK was related to myocardial fibrosis in DCM. 167 In addition, JNK was involved in regulating NLRP3 inflammasome activation in macrophages. 168 IL-1β, IL-6, and TNF-α could stimulate JAK/STAT after binding to the receptor, thereby initiating the expression of downstream inflammation-related target genes.…”
Section: Cytokines Impact On Heart Functionmentioning
confidence: 99%
“…JNK was a key upstream molecule of NF‐κB 165 and it could be activated by inflammatory cytokines such as TNF‐α, which induced IR 166 . TGF‐β1/JNK was related to myocardial fibrosis in DCM 167 . In addition, JNK was involved in regulating NLRP3 inflammasome activation in macrophages 168 .…”
Section: Inflammation‐mediated Complications In Diabetesmentioning
confidence: 99%
“…There were some studies that have shown significant reductions in myocardial interstitial fibrosis. Epigallocatechin gallate (EGCG), a natural antioxidant, reduced high glucoseinduced oxidative stress and inhibited cardiac interstitial fibrosis in a diabetic rat model [38]; Curcumin, a natural polyphenol, reduced oxidative stress and inhibited Akt/GSK-3βinduced fibrosis in a diabetic rat model [39]; and N-acetylcysteine (NAC), a glutathione precursor, reduced high glucose-induced oxidative stress and inhibited interstitial fibrosis in a diabetic mice model [40]. Melatonin, a natural antioxidant, and Resveratrol, a natural polyphenol, also reduced oxidative stress and inhibited myocardial interstitial fibrosis in a diabetic rat model [41].…”
Section: Ros-dependent Microvascular Inflammationmentioning
confidence: 99%
“…A study showed that EGCG and quercetin reduced insulin resistance, both in vivo and in vitro, and also reduced glucose metabolism in the liver [ 79 ]. A study in a rat model of diabetes showed that EGCG improved diabetes in rats and improved streptozotocin-induced complications [ 80 ]. Catechin is a naturally occurring product that has also been shown to have anti-diabetic activity.…”
Section: Classification Synthesis and Activity Of Flavonoidsmentioning
confidence: 99%